1998
DOI: 10.1021/jf980704g
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Forms of Red Wine Anthocyanins as Antioxidants

Abstract: Anthocyanins are one of the main classes of flavonoids in red wines, and they appear to contribute significantly to the powerful antioxidant properties of the flavonoids. In grapes and wines the anthocyanins are in the flavylium form. However, during digestion they may reach higher pH values, forming the carbinol pseudo-base, quinoidal-base, or the chalcone, and these compounds appear to be absorbed from the gut into the blood system. The antioxidant activity of these compounds, in several metal-catalyzed lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(106 citation statements)
references
References 16 publications
0
93
0
13
Order By: Relevance
“…A previous study reports the antioxidant activity of malvidin-3-glucoside that was determined by metal-catalyzed lipid peroxidation models in comparison with other antioxidants [30]. The result shows that the quinoidal-base and pseudo-base of malvidin-3-glucoside significantly inhibited peroxidation of linoleate by myoglobin compared with catechin.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous study reports the antioxidant activity of malvidin-3-glucoside that was determined by metal-catalyzed lipid peroxidation models in comparison with other antioxidants [30]. The result shows that the quinoidal-base and pseudo-base of malvidin-3-glucoside significantly inhibited peroxidation of linoleate by myoglobin compared with catechin.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 98%
“…During digestion, the flavylium ion is converting to carbinol pseudo-base, quinoidal-base, or the chalcone at increasing pH before being absorbed into the blood system [30]. As mentioned earlier, anthocyanin pigment appears to be red in acidic conditions and blue to purple in alkaline solutions.…”
Section: Anthocyanin Pigments As Food Colorants and Additivesmentioning
confidence: 99%
“…This can be attributed to the fact that during baking and frying, the bioactive compounds such as polyphenols and anthocyanins are degraded, affecting the antioxidant activity (Lapidot et al, 1999). Some studies have reported that the presence of polyphenolics such as catechin and free forms of ferulic acid in corn flours contribute to the antioxidant activity (De la Parra et al, 2007;López-Martínez et al, 2009).…”
Section: Texturementioning
confidence: 99%
“…El consumo de frutos y verduras esta asociado al bajo riesgo de incidencias y mortalidad de cáncer [7], y a menores índices de mortalidad por enfermedad coronaria [18,22], según se desprende de diversos estudios epidemiológicos. Los fenoles, especialmente los flavonoides [16] y los antocianos [9,16,24,31], muestran una gran capacidad para captar radicales libres causantes del estrés oxidativo, atribuyéndoseles a su vez un efecto beneficioso en la prevención de enfermedades tales como: cardiovasculares, circulatorias, cancerígenas y neurológicas [20,21,26,44,48,52]. Poseen actividades anti-inflamatoria, antialérgica, antitrombótica, antimicrobiana y antineoplá-sica [34,40,41,43].…”
Section: Introductionunclassified